Nudges Don't Work When the Benefits Are Ambiguous: Evidence from a High‐Stakes Education Program. (4th March 2021) - Castleman, Benjamin L.; Murphy, Francis X.; Patterson, Richard W.; Skimmyhorn, William L.
Abstract: The Post‐9/11 GI Bill allows service members to transfer generous education benefits to a dependent. We run a large‐scale experiment that encourages service members to consider the transfer option among a population that includes individuals for whom the transfer benefits are clear and individuals for whom the net‐benefits are significantly more ambiguous. We find no impact of a one‐time e‐mail about benefits transfer among service members for whom we predict considerable ambiguity in the action, but sizeable impacts among service members for whom education benefits transfer is far less ambiguous. Our work contributes to the nascent literature investigating conditions when low‐touch nudges at scale may be effective.